The Krasnouralsky profile in the Middle Urals, Russia: A tomographic approach to vintage DSS data - Kashubin, A.; Tryggvason, A.; Juhlin, Christopher; Rybalka, A.; Kashubina, T.; Shkred, I. (Elsevier BV, 2009)
The Middle Urals region has been widely studied with geophysical methods over the past decades. An integrated program is in progress to summarize this knowledge, including modern reprocessing of controlled-source seismic data. This work is devoted to the Krasnouralsky DSS profile. We applied modern tomography inversion algorithms in 2D and 2.5D on first break traveltime picks from an archive catalogue. A number of initial models and various smoothing constraints were used to investigate the influence of starting models on the final model. Robustness and uncertainty of the recovered models were estimated with hypothesis testing and checkerboard tests. The recovered velocity structure shows a thicker crust below the contact of the West Uralian Zone and the Central Uralian Zone and below the Tagil-Magnitogorsk Zone. Deep high velocity anomalies on both sides of this zone are interpreted as crustal thinning or alteration of the crust by intrusions of mantle material. Our results suggest that it is worthwhile reinterpreting DSS traveltime data with modern inversion techniques. © 2008 Elsevier B.V. All rights reserved.